Adult-onset Still's disease revealed by a complete atrioventricular block, totally regressive under corticosteroid therapy. Issue 3 (March 2020) - Piriou, Pierre-Guillaume; Plessis, Julien; Letocart, Vincent; Piriou, Nicolas; Probst, Vincent; Néel, Antoine
Abstract: We report the case of a 40-year-old veterinary surgeon who was admitted for spiking fevers, arthralgia, and a complete atrioventricular block. Tests revealed an inflammatory syndrome, hepatic cytolysis, neutrophilic leukocytosis, and increased troponin levels. Cardiac magnetic resonance imaging showed a small myocarditis but no tissue abnormality on the conduction pathways. In the absence of evidence-based infection and favorable evolution under broad spectrum antibiotherapy, an adult-onset Still's disease was suspected and corticosteroid therapy administered. Evolution was then impressively favorable, with a persistent sinus heart rhythm 3 days later. Learning objective: Febrile conductive disorders occurring during a systemic disorder with negative infection and auto-immunity work-up should lead to consider an adult-onset Still's disease, which can be treated and cured, especially with steroids. Moreover, fever, polyarthritis, neutrophilic leukocytosis, pericarditis, and myocarditis should lead to consideration of adult-onset Still's disease.